Kepedulian Siswa SMA Negeri 1 Sutera Dalam Menjaga Kebersihan Lingkungan Sekolah Di Kenagarian Surantih Kecamatan Sutera Kabupaten Pesisir Selatan - Hilmania, Yolla - (Pendidikan Geografi, 2014)
This study aimed to describe: (1) how the students role in maintaining the cleanliness ofthe school environment in order to always look clean. (2) how the students motivation tomaintain a healthy school environment. (3) how the social environment in keeping theenvironment clean.This research is a descriptive study that sought to describe a situation for what it is. Thepopulation in this study was a high school student Silk N 1 totaling 544 people. The sample inthis study using proportional random sampling technique. So the study sample totaled 87 people.The instrument used in this study was a questionnaire. As for the use of data analysis techniquespercentage.The results of this study revealed that: (1) the role of students in the school in order tokeep the environment clean is always seen students do not have a role in maintaining a schoolenvironment that allow garbage strewn, never carry picket class, do not implement the rules setschool and let the garbage away . (2) the students motivation to maintain a healthy schoolenvironment a lack of awareness of the students to create a school environment that is clean isstill a lot of littering and creating clean air. (3) the social environment in maintaining thecleanliness of the environment, including on the issue of the lack of partisifasi of the communityto maintain the environment so as to feel uncomfortable and causes beta does not stay a lack ofawareness of the community to work together to clean up their social environment and the lack offacilities and infrastructure within the schools is not sufficient .